Targeting Regulatory T Cells for Therapy of Lupus Nephritis - Venkatadri, Rajkumar; Sabapathy, Vikram; Dogan, Murat; Sharma, Rahul (Frontiers in Pharmacology, 2022)
Lupus glomerulonephritis (LN) is a complex autoimmune disease characterized by circulating autoantibodies, immune-complex deposition, immune dysregulation and defects in regulatory T cell (Tregs). Treatment options rely on general immunosuppressants and steroids that have serious side effects. Approaches to target immune cells, such as B cells in particular, has had limited success and new approaches are being investigated. Defects in Tregs in the setting of autoimmunity is well known and Treg-replacement strategies are currently being explored. The aim of this minireview is to rekindle interest on Treg-targeting strategies. We discuss the existing evidences for Treg-enhancement strategies using key cytokines interleukin (IL)-2, IL-33 and IL-6 that have shown to provide remission in LN. We also discuss strategies for indirect Treg-modulation for protection from LN.